Effects of temperature steps on human health and thermal comfort. (December 2015) - Xiong, Jing; Lian, Zhiwei; Zhou, Xin; You, Jianxiong; Lin, Yanbing
Abstract: Human beings are often likely to expose themselves to sudden temperature change in daily life. For example, when entering/exiting an air-conditioned building from/to outdoors people may suffer not only thermal discomfort but also even some potential health problems. In this study, the influence of different air temperature step-changes (S5:32°C-37°C-32 °C, S11:26°C-37°C-26 °C, and S15:22°C-37°C-22 °C) on human health and thermal comfort was studied with 24 volunteered participants in the laboratory experiment. Results show that perspiration, eyestrain, dizziness, accelerated respiration and heart rate are sensitive self-reported symptoms in response to temperature step-changes. Thermal sensation, comfort and acceptability just before temperature step are significantly distinguished from that immediately after step change except for thermal comfort and acceptability in up-step of S15 (22 °C-37 °C). Hysteresis phenomenon appears when subjects move from neutral to warm environment. Psychological lead occurs after both up-steps and down-steps. Temperature step magnitude and changing direction have significant impact on human response to temperature steps. Highlights: Sensitive self-reported health symptoms and fatigue subtypes were found. The phenomena of psychological lead and hysteresis were observed. Asymmetry of human response occurred in temperature step-change environment. Time to stabilize for skin temperature after temperature steps was analyzed.